2003
DOI: 10.1002/anie.200219877
|View full text |Cite
|
Sign up to set email alerts
|

From Angstroms to Micrometers: Self‐Organized Hierarchical Structure within a Polymer Film

Abstract: Self‐organization on three length scales is exhibited by a block copolymer of styrene and an oligothiophene‐bearing isoprene in cast films. For example, a phase‐separated nanostructure consisting of π‐conjugated oligothiophene molecules is self‐aligned perpendicular to the substrate, as revealed in a TEM image of a section through the film (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
134
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(134 citation statements)
references
References 21 publications
0
134
0
Order By: Relevance
“…Furthermore, various micro structures such as pincushion structures, 10 microsphere arrays 11 and so on were fabricated based on secondary processing of the honeycomb-patterned films. Wide variety of materials, including block copolymers, [12][13][14][15] star polymers, [16][17][18] dendrimers 19 can be used to prepare the honeycomb-patterned films. Amphiphilic copolymers (polyacrylamide, 20 polyion complex 21 ) are suitable polymers for preparation of the honeycomb-patterned films.…”
mentioning
confidence: 99%
“…Furthermore, various micro structures such as pincushion structures, 10 microsphere arrays 11 and so on were fabricated based on secondary processing of the honeycomb-patterned films. Wide variety of materials, including block copolymers, [12][13][14][15] star polymers, [16][17][18] dendrimers 19 can be used to prepare the honeycomb-patterned films. Amphiphilic copolymers (polyacrylamide, 20 polyion complex 21 ) are suitable polymers for preparation of the honeycomb-patterned films.…”
mentioning
confidence: 99%
“…20 We reported a semi-rod-coil type block copolymer, polystyreneb-polyisoprene with oligothiophene-modified side chains (PS-b-POTI) and the hierarchically structure within the film which prepared from the polymer solution by casting under a moist air flow. 21 Three tiers of the ordered empty micropores, the walls of which cony To whom correspondence should be addressed (Tel: +81-3-5734-2429, Fax: +81-3-5734-2875, E-mail: hayakawa@op.titech.ac.jp).…”
mentioning
confidence: 99%
“…Resulting micropores were hexagonally packed with the narrow size distribution. It is believed that the formation of the microporus structure originates from the presence of condensed water droplets on the solvent evaporation [9][10][11][12][13]. The diameter of the open pores on the surface was dependent on the flow rate.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally it is recently observed that rod-coil block copolymers [9][10][11] as well as amphiphilic polymers [12,13] spontaneously form ordered microporous structures with a variety of length scale, when the polymer solutions are cast under humid conditions. In the case of a specially designed block copolymer, resulting porous films have highly ordered hierarchical structures over multiple length scales from angstroms to micrometers [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation